A influência do gênero do discurso na mente do consumidor: uma análise pelas teorias do duplo processamento - Novais, Ana Lúcia Moura (2019)
This doctoral dissertation is focused on both study and analysis of discourse gender in consumer’s cognitive process, leading him/her to make judgments in intuitive or cognitive ways. As for the cognitive process, that establishes judgments and leads to decision making, the dual process theories (DPT) were developed in the field of psychology, and they sustain, in essence, the existence of a process and a set of actions generated intuitively or rationally when exposed to something. The aim of this doctoral dissertation is the creation of a model to identify the discourse gender in a way it arouses the cognitive process of individuals before texts, influencing their judgment and decision making. The study consists of research on satisfaction/dissatisfaction perception of consumers that wrote reviews in Amazon.com about books of different authors and time, organized in two thematic groups, one containing reviews of classic novels of North-American literature and the other about classic novels of British literature. The selection of reviews in those two thematic groups is justified by their differences regarding literary tradition, because of the nationality of the writers, as well as linguistic variations, along with aspects related to sociocultural and historical contexts. The criteria in determining the sample were grounded in the choice of books with the most substantial amount of reviews, and those refer to three North-American novels and other three British novels. In a total of 100,000 reviews, the final sample was 8,378. This dissertation uses procedures of qualitative analysis, with the social constructivist conception approach to understanding the different significations of individuals related to objects or understanding or various aspects. In the context of this research work, the discourse gender theory is a way to understand the characteristics of the reviews text conception. Due to the nature of this study, a content analysis methodology is also used. From the sample of both North-American and British Literature reviews, consumers with higher involvement by the novel elaborate reviews with superior analytic density, deeper associations, while consumers with difficulties in understanding a specific novel, elaborate reviews with lower analytic density and are more inclined to describe their negative impressions, moved by the description of their effort or suffering while reading that novel